Evolutionary divergence of neuroanatomical organization and related genes in chimpanzees and bonobos. (September 2019) - Staes, Nicky; Smaers, Jeroen B.; Kunkle, Amanda E.; Hopkins, William D.; Bradley, Brenda J.; Sherwood, Chet C.
Abstract: Given their close genetic relatedness to humans, bonobos ( Pan paniscus ) and chimpanzees ( Pan troglodytes ) offer an essential comparative framework for studying the evolution of uniquely human traits. These two species differ markedly in their socio-behavioral repertoires, which is reflected in neuroanatomical differences that have been reported in the literature. However, phylogenetic comparative methods have not yet been used to map the evolution of neuroanatomical traits in bonobos and chimpanzees, limiting our ability to understand which neural systems are derived in each species in relation to the last common ancestor of Pan ( Pan- LCA). Here, we examine evolutionary changes in neuroanatomical traits of bonobos and chimpanzees relative to ancestral character reconstructions of the Pan -LCA using comparative datasets from hominoids. We found that bonobo brains are derived in showing reduction of whole brain and white matter volumes, with particularly striking reduction of male brain size compared to the inferred Pan -LCA value. Brain structures related to social cognition and emotional regulation, like the insular cortex and amygdala, display a mosaic pattern of evolution with certain traits changing to a greater extent in each species. Examination of potential genetic mechanisms underlying divergence of neural and social traits did not reveal clear differences in protein evolution patterns between the two species. These findings suggest that the brain anatomy of extant bonobos and chimpanzees show lineage-specific specializations and neither can be considered to more closely retain the ancestral state of Pan . Consequently, this raises questions about the extent that modern chimpanzees or bonobos may serve as referential models for the neuroanatomy of the LCA of humans and apes.